BLOOD GLUCOSE LEVELS AND THE MICROSCOPIC STRUCTURE OF KIDNEY WISTAR RAT DIABETES MELLITUS UNDER THE EFFECT OF LAWSONIA INERMIS (LINN.) LEAVES ETHANOLIC EXTRACT - Sari, Mutiara Indah; Antika, Maya Anjelir; Anggraini, Dwi Rita (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Lawsonia inermis (Linn.) leaves are one of the alternative medicines to treat diabetes mellitus in Indonesia. We investigated the blood glucose level (BGL) of the L. inermis (Linn.) leaves ethanolic extract (LLEE) leaves and evaluated the histopathological alterations in diabetic rats. Methods: This study was an experimental study with posttest - only control group design. Alloxan (120 mg/kg, intraperitoneally)-induced diabetic rats. 35 of Wistar rats (Rattus norvegicus) were divided randomly into five groups, i.e. K: Normal control, P1: Diabetic control, and P2, P3, and P4 (200 mg/kg body weight [BW], 400 mg/kg BW, and 600 mg/kg BW of LLEE, orally) for 28 days. At the end of the treatment, the rats were sacrificed to obtain the kidney for histopathological evaluation using hematoxylin and eosin technique. BGLs were conducted using a glucose meter (GlucoDR). Results: One-way ANOVA test showed that dose 400 mg/kg BW of the LLEE was related to BGL of alloxan-induced diabetic rats (p=0.000). The histopathological of kidney showed glomerular inflammation (GI), epithelial membrane lining degeneration, vascular congestion, and interstitial tubule hemorrhage at diabetic control (P1). Meanwhile, treated with 600 mg/kg BW of LLEE (P4) showed increase cellular regeneration as normal architecture of the kidney. Conclusion: The LLEE at dose 400 mg/kg BW effective decreased BGL and was able to restore the kidney destruction of alloxan-induced diabetic rats at dose 600 mg/kg BW.